RADT-28. MULTI-SESSION RADIOSURGERY FOLLOWING SURGERY FOR INTRACRANIAL MENINGIOMAS: 10-YEAR OUTCOMES FROM A SINGLE INSTITUTION PROTOCOL. (14th November 2022) - Carrasquilla, Michael; Cantalino, Jonathan; Hay, Kathryn; Chesney, Kelsi; Sayah, Anousheh; Sloan, Emily; Watson, Joseph; Anaizi, Amjad; Jean, Walter; McGrail, Kevin; Collins, Sean; Collins, Brian
Abstract: INTRODUCTION: Meningioma is the most common adult primary intracranial tumor. Surgical resection is the favored treatment with radiotherapy often utilized for residual or recurrent disease. Long-term outcomes are well-established for single-session radiosurgery but mature outcomes for multisession radiosurgery do not yet exist. We report our institution's 10-year efficacy and toxicity outcomes for 5-fraction radiosurgery following surgical resection of intracranial meningiomas. METHODS: All intracranial meningioma patients treated at our institution between 2002-2018 with 5-fraction radiosurgery following surgery were eligible for inclusion. Standard variables were analyzed to predict local failure and overall survival. RESULTS: Forty-one consecutive patients with a female predominance (76%) and median age of 58 years (range: 27–84) were included. Thirty benign (73%) and 11 atypical meningiomas (27%) with a median gross tumor volume of 7.79cc (range: 0.38-52.63) were treated. All patients completed radiosurgery for residual tumor (41%) or recurrent disease (59%). A median dose of 3000cGy (range: 2500-3500cGy), was delivered to a median isodose line of 82% (range: 71%-90%). The median follow-up from the date of surgery was 10 years. Nine tumors (22.0%) progressed following radiosurgery. The local control rate at 10-years was significantly better for benign tumors than atypical tumors (93% vs 27%, p = 0.001). Factors found to be predictive of local failure on multivariate analysis were tumor grade (HR: 13.8, p = 0.002) and tumor volume (HR: 1.08, p = 0.031). For benign tumors all failures occurred at the margin of the unirradiated tumor bed, while atypical tumors failed predominately in-field (71%). Three patients with atypical meningioma developed radiation necrosis following aggressive treatment (3500cGy). Overall survival at 10-years was 93% for benign tumors and 60% for atypical tumors (p = 0.026). CONCLUSION: Multisession radiosurgery following surgery for benign intracranial meningiomas provides excellent long-term tumor control with minimal toxicity. However, for atypical meningiomas this approach results in poor local control.